Особливості розподілу жирової тканини у хворих на цукровий діабет 2-го типу з ожирінням та артеріальною гіпертензією - Зуєв, К. О. (Clinical Endocrinology and Endocrine Surgery, 2013)
The research, studied the correlation between mass of adipose tissue (its distribution at the abdominal and gluteofemoral areas) and the anthropometric indexes (body mass index (BMI), waist circumference (WC), hip circumference (HC) and waist-hip ratio) of 53 patients with diabetes mellitus type 2, with obesity and arterial hypertension. Determination of adipose tissue distribution in the body was conducted by the method of dual-energy X-ray absorptiometry and routine anthropometric measuring. ANOVA analysis revealed the differences in general and local body fat mass distribution and some antropometric characteristics related with patients' gender. Application of regression analysis showed the positive association of BMI with body mass of adipose tissue, as well as with adipose tissue localized in abdominal and gluteofemoral areas. It is necessary to take into account that sexual dimorphism and inherited factors mostly predetermine the fat distribution at waist and hips as well as WHR when use the above mentioned anthropometric indexes for the estimation of degree and type of obesity. The conclusion about close relation between some anthropometric indexes and indexes of body fat mass, evaluated by dual-energy X-ray absorptiometry, is observed when the general mass of adipose tissue does not exceed 50% of body weight.